How Our Continuing Studies of the Pre-clinical Inbred Mouse Models of Mesothelioma Have Influenced the Development of New Therapies - Robinson, Bruce W.S.; Redwood, Alec J.; Creaney, Jenette (Frontiers in Pharmacology, 2022)
Asbestos-induced preclinical models of mesothelioma produce tumours that are very similar to those that develop in humans and thus represent an ideal platform for translation into the clinic as the basis for novel clinical trials. These have ranged from chemotherapy to immunotherapy and combinations, as well as other new approaches to what was initially seen as an incurable cancer. These models and studies have led to trials which have improved the response rate in mesothelioma from less than 10% to over 50%. The future success of mesothelioma immunotherapy is founded on such models.